2004
DOI: 10.1289/ehp.6857
|View full text |Cite
|
Sign up to set email alerts
|

Does Particulate Air Pollution Contribute to Infant Death? A Systematic Review

Abstract: There is now substantial evidence that both short- and long-term increases in ambient air pollution are associated with increased mortality and morbidity in adults and children. Children’s health is particularly vulnerable to environmental pollution, and infant mortality is still a major contributor to childhood mortality. In this systematic review we summarize and evaluate the current level of epidemiologic evidence of an association between particulate air pollution and infant mortality. We identified releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 52 publications
0
58
2
1
Order By: Relevance
“…In recent years, researchers are finding it worthy to investigate potential links between PM 2.5 exposure and adverse birth outcomes (Slama et al, 2008;Dadvand et al, 2013), epigenetic alteration (Baccarelli et al, 2008;Salam et al, 2012;Byun et al, 2013;Hou et al, 2013) infant mortality (Woodruff et al, 1997;Lipfert et al, 2000;Dales et al, 2004;Glinianaia et al, 2004) atherosclerosis (Araujo et al, 2008;Araujo, 2011;Kaufman, 2011), stroke (Brook, 2008;Brook andRajagopalan, 2009, 2012;Maheswaran et al, 2010Maheswaran et al, , 2012, rheumatic autoimmune disease (Zeft et Table 1. Particulate matter and health outcomes for PM 10 , PM 2.5 and ultrafine particles (UFPs).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers are finding it worthy to investigate potential links between PM 2.5 exposure and adverse birth outcomes (Slama et al, 2008;Dadvand et al, 2013), epigenetic alteration (Baccarelli et al, 2008;Salam et al, 2012;Byun et al, 2013;Hou et al, 2013) infant mortality (Woodruff et al, 1997;Lipfert et al, 2000;Dales et al, 2004;Glinianaia et al, 2004) atherosclerosis (Araujo et al, 2008;Araujo, 2011;Kaufman, 2011), stroke (Brook, 2008;Brook andRajagopalan, 2009, 2012;Maheswaran et al, 2010Maheswaran et al, , 2012, rheumatic autoimmune disease (Zeft et Table 1. Particulate matter and health outcomes for PM 10 , PM 2.5 and ultrafine particles (UFPs).…”
Section: Introductionmentioning
confidence: 99%
“…A relationship between ambient air pollution and daily mortality and morbidity rates has been reported for many cities throughout the world (Schwela, 2000;Stieb et al, 2002;Glinianaia et al, 2004;Gordon et al, 2004). The relevant contaminants include sulfur dioxide, suspended particulate matter, nitrogen dioxide, carbon monoxide, ozone, and lead (Schwela, 2000).…”
Section: Ambient Air Exposure Pathwaymentioning
confidence: 94%
“…due to poor maternal malnutrition) increases risk of coronary heart disease in adulthood (Lau & Rogers, 2005) Decreased cell-mediated immunity in males following perinatal exposure of rats to methoxychlor (Chapin et al, 1997) and heptachlor (Smialowicz et al, 2001;Smialowicz, 2002) Lead exposure reduces Th1 immune capability, causing a shift towards increased Th2 responses in rats Dietert & Lee, 2005) Altered airway growth with increased collagen deposition in airway walls with exposure to maternal smoking (Sekhon et al, 2001) Altered control of breathing with diminished hypoxic response postnatally with maternal smoking in utero (Ueda et al, 1999) Inorganic arsenic in drinking-water caused adrenal tumours in male offspring and ovarian and lung tumours in female offspring as adults (Waalkes et al, 2003) (Glinianaia et al, 2004) Child Leukaemia in children due to radiation from atomic bomb (IARC, 2000) Ionizing radiation and leukaemia in childhood and adulthood (Chow et al, 1996;Ron et al, 1988a) Radioisotopes of iodine from Chernobyl disaster and thyroid carcinoma (Pacini et al, 1997) Adolescent Exacerbation of preexisting asthma from exposure to particulates in the air (Parnia et al, 2002) Chronic ozone exposure decreases lung function (Kunzli et al, 1997) Breast cancer in adulthood with high-dose ionizing radiation (Boice et al, 1996) ACE, angiotensin converting enzyme; AGD, anogenital distance; DES, diethylstilbestrol; IUGR, intrauterine growth restriction; PBBs, polybrominated biphenyls; PCBs, polychlorinated biphenyls; T3, triiodothyronine; T4, thyroxine; TCDD, tetrachlorodibenzo-p-dioxin; Th1 development; however, where there was good supporting evidence from animal models or where particular...…”
Section: Fetusmentioning
confidence: 99%
See 1 more Smart Citation
“…[63][64][65][66] DEPs caused a significant decrease in adult sperm production and a diminished number of Sertoli cells in an animal model. 67 Other studies have shown aberration of sex hormone production and effect in chronically exposed female rats, with increased levels of testosterone and subsequent masculinization.…”
Section: Perinatal Health and Infertilitymentioning
confidence: 99%